Analisis Break Even Point dan Faktor yang Mempengaruhi Usaha Tahu pada Masa Pandemi Covid-19 di Kecamatan Tolangohula Kabupaten Gorontalo - Mahalipa, Harija K; Indriani, Ria; Wibowo, Larasati Sukmadewi; Imran, Supriyo (Journal Galung Tropika, 2022)
This study aims to determine the break-even point and analyze the factors influencing tofu business income in Tolangohula District, Gorontalo Regency. This research approach uses quantitative methods. Methods of data collection using questionnaires/questionnaires and interview techniques. The results showed that the quantity in tofu production before the Covid-19 pandemic, when the break-even point began with the production BEP, acceptance BEP and price BEP were 34 boards, Rp. 1,187,552/month and Rp. 20,611/board. During the Covid-19 pandemic, when the production BEP break-even point, revenue BEP, and price BEP were 56 boards, Rp. 2,267,145/month and Rp. 31,518/board. Factors affecting the tofu business in Tolangohula District, Gorontalo Regency, have been tested simultaneously: labor, the selling price of tofu, production costs, and soybean production to income.